Tobacco Thrips Frankliniella fusca (Hinds) (Insecta: Thysanoptera: Thripidae) - Ethan Carter; Jennifer L. Gillett-Kaufman (EDIS, 2015)
This document provides an overview of the tobacco thrips, Frankliniella fusca, detailing its distribution, description, life cycle, host plants, economic importance, and management strategies. Tobacco thrips are small insects that feed on various plants, causing damage and transmitting tospoviruses like Tomato spotted wilt virus. The life cycle includes egg, larval, prepupal, pupal, and adult stages. Management strategies include insecticide applications, biological control agents, and planting techniques. The document highlights the economic impact of tobacco thrips on crops and the challenges in controlling their populations.